2012
DOI: 10.1590/s0034-737x2012000500019
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento da mandioca e plantas daninhas em resposta à adubação fosfatada

Abstract: Growth of cassava and weed in response to phosphate fertilizerFertilizers may be used to change the competitive relations, favoring the crop species, providing the competing species have different responses to the nutrient application. Thus, the aim of this study was to evaluate the growth of Cassava plant, Bidens pilosa L. and Brachiaria decumbens Stapf, as a function of the amount of P supplied at planting. The experiment was conducted in a greenhouse and the, treatments were arranged in a 3 x 4 factorial, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
(10 reference statements)
1
7
0
7
Order By: Relevance
“…A similar behavior was observed by Pereira et al (2012), in which was found out that while evaluating the growth of cassava and weeds in response to phosphorous fertilization the fertilization tends to contribute to a faster growing rate for weeds than for cassava. To Carvalho et al (2007a), there is a greater development of the roots in the initial periods of the development cycle of weeds, resulting in an increase of nutrient uptake by radicular interception, leading to a quick accumulation of nutrients by the roots and, consequently, a lower availability for the crop.…”
Section: Resultssupporting
confidence: 78%
“…A similar behavior was observed by Pereira et al (2012), in which was found out that while evaluating the growth of cassava and weeds in response to phosphorous fertilization the fertilization tends to contribute to a faster growing rate for weeds than for cassava. To Carvalho et al (2007a), there is a greater development of the roots in the initial periods of the development cycle of weeds, resulting in an increase of nutrient uptake by radicular interception, leading to a quick accumulation of nutrients by the roots and, consequently, a lower availability for the crop.…”
Section: Resultssupporting
confidence: 78%
“…The P uptake model is corroborated by the production of roots per plant that presented the linear model (Figure 2g). Linear response of cassava roots production as a function of a larger availability of P in the soil was observed by Pereira et al (2012).…”
Section: Resultsmentioning
confidence: 90%
“…O uso de adubação para o aumento de produção é de suma importância, principalmente para que haja um bom desenvolvimento radicular das plantas (VALDEMAR & FLÁVIA, 2012). Uma das práticas edáficas que tem demonstrado maiores índices de produtividade e consequentemente retorno econômico é a realização da adubação fosfatada na lavoura de mandioca (PEREIRA et al, 2012). No Brasil a mandioca apresenta uma baixa produtividade, sendo de 15 t ha -1 a estimativa para 2016 (IBGE, 2016).…”
Section: Introductionunclassified